2011
DOI: 10.1016/j.bmc.2011.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and biological evaluation of callophycin A and analogues as potential chemopreventive and anticancer agents

Abstract: Callophycin A was originally isolated from the red algae Callophycus oppositifolius and shown to mediate anticancer and cytotoxic effects. In our collaborative effort to identify potential chemopreventive and anticancer agents with enhanced potency and selectivity, we employed a tetrahydro-β-carboline-based template inspired by callophycin A for production of a chemical library. Utilizing a parallel synthetic approach, 50 various functionalized tetrahydro-β-carboline derivatives were prepared and assessed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…carbolines have been reported to inhibit NO production in macrophages (Lee et al, 2000;Yoon et al, 2005) and other cell types (Newton et al, 2007;Shen et al, 2011;Wong et al, 2011), this biologic activity has typically been associated with suppressed NF-kB activity (Lee et al, 2000;Yoon et al, 2005;Wen et al, 2006;Newton et al, 2007;Shen et al, 2011;Oh et al, 2013) and reduced expression of cytokines and other inflammatory genes transcriptionally regulated by NF-kB (Newton et al, 2007;Oh et al, 2013). A recent screen of 50 functionalized tetrahydro-b-carboline derivatives (Shen et al, 2011) reported that the most potent carboline derivative had IC 50 values for inhibition of NF-kB activity and NO production of 4.8 and 2.8 mM, respectively.…”
Section: -Gly Carb Inhibits No Formation In Macrophagesmentioning
confidence: 99%
See 2 more Smart Citations
“…carbolines have been reported to inhibit NO production in macrophages (Lee et al, 2000;Yoon et al, 2005) and other cell types (Newton et al, 2007;Shen et al, 2011;Wong et al, 2011), this biologic activity has typically been associated with suppressed NF-kB activity (Lee et al, 2000;Yoon et al, 2005;Wen et al, 2006;Newton et al, 2007;Shen et al, 2011;Oh et al, 2013) and reduced expression of cytokines and other inflammatory genes transcriptionally regulated by NF-kB (Newton et al, 2007;Oh et al, 2013). A recent screen of 50 functionalized tetrahydro-b-carboline derivatives (Shen et al, 2011) reported that the most potent carboline derivative had IC 50 values for inhibition of NF-kB activity and NO production of 4.8 and 2.8 mM, respectively.…”
Section: -Gly Carb Inhibits No Formation In Macrophagesmentioning
confidence: 99%
“…A recent screen of 50 functionalized tetrahydro-b-carboline derivatives (Shen et al, 2011) reported that the most potent carboline derivative had IC 50 values for inhibition of NF-kB activity and NO production of 4.8 and 2.8 mM, respectively. In comparison, the IC 50 value of 8-Gly carb for inhibition of NO production (∼7 mM) is similar, but the IC 50 value of 8-Gly carb for inhibition of NF-kB activity would exceed 100 mM.…”
Section: -Gly Carb Inhibits No Formation In Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8] Recently, more attention has been focused on the study of the tetrahydro-β-carboline derivatives about their potential antitumor activities. 4,5,9,10) Current issues in cancer research show that many tricyclic ring carboline compounds which display potent cytotoxicity against numerous cancer cell lines are harman and norharman derivatives, 11) and more complex structures such as manzanine, 12) azatoxin, 13) eudistomine K, 14) fascaplysine, 15) and picrasidine L. 16) Therefore, the structural fragment of tetrahydro-β-carboline seems to be essential for many biologically important indole alkaloids and represents an important lead structure for the development of novel anticancer agents.In an ongoing study on discovering new anti-tumor agents for human use, we were inspired by the fact that hydroxylcinnamic acids, such as ferulic acid and p-hydroxy-cinnamic acid, are known as phenolic compounds occurring in natural plant product, and their derivatives displayed selective antiproliferative activity against some types of cancer cells, [17][18][19] which attracts considerable attention from medicinal chemists.There is an increased interest in the use of hybrid molecules for drug discovery against a multitude of disease indications.20,21) Many tetrahydro-β-carboline hybrids bearing cinnamoyl or aroyl group at the N2 position, reported in recent literatures, exhibit excellent biological acitivities. 22,23) With these ideas in mind, we conjugated tetrahydro-β-carboline alkaloid with hydroxylcinnamic acid and different nitrogencontaining heterocycle was introduced to positions-N9 of tetrahydro-β-carboline through carbonchain with the purpose for the improvement of water-solubility.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8] Recently, more attention has been focused on the study of the tetrahydro-β-carboline derivatives about their potential antitumor activities. 4,5,9,10) Current issues in cancer research show that many tricyclic ring carboline compounds which display potent cytotoxicity against numerous cancer cell lines are harman and norharman derivatives, 11) and more complex structures such as manzanine, 12) azatoxin, 13) eudistomine K, 14) fascaplysine, 15) and picrasidine L. 16) Therefore, the structural fragment of tetrahydro-β-carboline seems to be essential for many biologically important indole alkaloids and represents an important lead structure for the development of novel anticancer agents.…”
mentioning
confidence: 99%